The impact of leader safety communication on work engagement under pandemic: The effect of OBSE and anxiety based on COVID-19 - Zhou, Xingchi; Guo, Yujie; Liu, Yuhao (Frontiers in Public Health, 2023)
The outbreak of COVID-19 has a great impact on employees’ daily work and psychology. Therefore, as leaders in organization, how to alleviate and avoid the negative impact of COVID-19 so that employees can maintain a positive working attitude has become a problem to be worthy paying attention. Based on Job Demands-Resources (JD-R) model, this paper investigates the relationship between leader safety communication based on COVID-19 and work engagement, and examines the mediating role of organization-based self-esteem and the moderating role of anxiety based on COVID-19. In this paper, we adopted a time-lagged cross-sectional design to test our research model empirically. The data from a sample of 264 participants in China were collected using existing scales in recent studies, and were used for testing our hypothesizes. The results show that leader safety communication based on COVID-19 will positively affect employees' work engagement (b = 0.47, p < 0.001), and organization-based self-esteem plays a full mediating role in the relationship between leader safety communication based on COVID-19 and work engagement (0.29, p < 0.001). In addition, anxiety based on COVID-19 positively moderates the relationship between leader safety communication based on COVID-19 and organization-based self-esteem (b = 0.18, p < 0.01), that is, when anxiety based on COVID-19 is at higher level, the positive relationship between leader safety communication based on COVID-19 and organizational-based self-esteem is stronger, and vice versa. It also moderates the mediating effect of organization-based self-esteem on the relationship between leader safety communication based on COVID-19 and work engagement as well (b = 0.24, 95% CI = [0.06, 0.40]). Theoretical and practical implications are given as well.